2020
DOI: 10.3390/molecules25010195
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Mesoporous Silica Nanoparticles Grafted with 2-(tert-butylamino)ethyl Methacrylate-b-poly(ethylene Glycol) Methyl Ether Methacrylate Diblock Brushes as Drug Nanocarrier

Abstract: This paper introduces the synthesis of well-defined 2-(tert-butylamino)ethyl methacrylate-b-poly(ethylene glycol) methyl ether methacrylate diblock copolymer, which has been grafted onto mesoporous silica nanoparticles (PTBAEMA-b-PEGMEMA-MSNs) via atom transfer radical polymerization (ATRP). The ATRP initiators were first attached to the MSN surfaces, followed by the ATRP of 2-(tert-butylamino)ethyl methacrylate (PTBAEMA). CuBr2/bipy and ascorbic acid were employed as the catalyst and reducing agent, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The mesopores size was estimated from the TEM image to be ca. 6 nm, which is larger than those of typical mesoporous silica nanoparticles, due to the pore expanding effect of nonpolar n-hexane [15,36]. All samples of bare MSNs, AP-MSNs, Gly-MSNs, and IDA-MSNs were characterized using BET.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…The mesopores size was estimated from the TEM image to be ca. 6 nm, which is larger than those of typical mesoporous silica nanoparticles, due to the pore expanding effect of nonpolar n-hexane [15,36]. All samples of bare MSNs, AP-MSNs, Gly-MSNs, and IDA-MSNs were characterized using BET.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…Nam-Kyoung et al reported the synthesis of a novel pH-triggered drug delivery system by grafting poly-L-lysine on the pore entrances of MSNs as a drug gatekeeper [ 31 ]. In addition, the synthesis of a pH-responsive diblock copolymer, i.e., 2-( tert -butylamino)ethyl methacrylate- b -poly(ethylene glycol) methyl ether methacrylate, was reported by Alswieleh et al [ 32 ]. Doxycycline was loaded in the multifunctional pH-responsive diblock copolymer, and the drug could be released from the nanosystem in a relatively controlled manner.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the versatility of MSNs can be improved by surface functionalization via various types of polymeric materials such as PEG, PEI, and PAMAM [ 153 ]. The silica polymer core/shell nanohybrids will enhance transfer efficiency and have a huge improvement particularly in controlled drug delivery [ 154 ]. Li et al [ 155 ] described a siRNA delivery system (M-MSN_VEGF siRNA@PEI-KALA), the magnetic MSNs (M-MSNs) were functionalized by PEI and peptide (KALA).…”
Section: Protective Carriers For Sirna Deliverymentioning
confidence: 99%